Dispositions : reframing teaching and learning - Costa, Arthur L; Kallick, Bena (Thousand Oaks, California : Corwin, a Sage Company, 2014)
'A costly gap exists between what we claim to value as educational essentials and how we evaluate results. In Dispositions, Arthur L. Costa and Bena Kallick present a game-changing look at why and how to'mind the gap''.- Cover
1. Introduction: Challenging the Mindset -- 2. Why Dispositions? -- 3. What are Dispositions? -- 4. Deciding On Dispositions -- 5. Dispositions: Hard-Wired or Learned? -- 6. Dispositions by Intention: Mapping the Curriculum -- 7. Observing and Assessing Growth in Dispositional Learning -- 8. School Cultures that Support Dispositional Learning -- *9. Afterthoughts and Actions
Includes bibliographical references and index.
Keywords: Education -- Aims and objectives; Educational psychology; Educational change